LOCAL ELECTIONS IN THE MUNICIPALITY OF LEPOSAVIĆ FROM 1992 TO 2024 (Heritage, 2025)
The aim of this paper is to give as complete a picture as possible of local elections in the municipality of Leposavić since the restoration of the multi-party system in the Republic of Serbia in the early 1990s. The municipality of Leposavic has an interesting political history. In 1912, the part was freed from Turkish rule and became part of the Serbian state, and in 1953 it was incoporated to the Autonomous Kosovo-Metohija region, and for a long time it was de facto the only exclusively serbian area in the AP of Kosovo and Metohija. After the arrival of the international administration in 1999, the municipality of Leposavić, like other Serbian communities in Kosovo and Metohija, found itself in a specific situation in which there was a duality of power, until the signing of the "Brussels Agreement" in 2013, which included this local self-government in a number of communities that belong to the still unformed Community of Serbian Municipalities. New tensions will arise in 2022 when Serbian representatives leave the local institutions of the temporary self-governing bodies of the administration in Pristina, due to persistent and repeated threats that the Association of Serbian Municipalities will not be formed. Due to the mentioned facts, the undoubted importance of Leposavić gives us reason to examine the electoral will of its inhabitants, according to often changed contextual conditions.
Keywords: Leposavić, Republic of Serbia, Kosovo and Metohija, local elections, political parties